Bridging the gap? Public–private partnerships and genetically modified crop development for smallholder farmers in Africa - Brian Dowd‐Uribe; Joeva Sean Rock; Trevor Spreadbury; Patricia Chiril; David Uminsky (Plants, People, Planet, 2024)
Societal Impact Statement Genetically modified (GM) crops have the potential to address multiple challenges for African smallholder farmers but are limited by several institutional constraints. Public–private partnerships (PPPs) are seen as an organizational fix to one such constraint, bringing privately held intellectual property rights on key crop technologies to African public institutions to develop GM crops for smallholder farmers. Here, a new comprehensive dataset of GM crops in Africa is used to understand the extent and efficacy of PPP‐led GM crop development for smallholder farmers and discuss what might limit their potential in the future. Summary Genetically modified (GM) crops are promoted as a key tool to address multiple challenges in Africa, including the impacts of climate change and food insecurity. Observers have noted, however, significant institutional challenges to achieving such goals, most notably, intellectual property rights (IPR) to key GM traits being held by private companies who have limited incentives to develop those technologies for smallholder farmers. To bridge the gap between privately held IPR and pro‐poor crop breeding, advocates have called for increased funding for institutional innovations such as public–private partnerships (PPPs) to facilitate the transfer of crop technologies from private companies to public research institutes. For the past two decades, donors and firms have invested considerable resources toward PPPs. However, to date, few research efforts have empirically examined the extent and effectiveness of PPPs at the continental scale. This study draws from a new comprehensive dataset on GM crop research and development in Africa to examine whether the anticipated advantages of PPPs have resulted in an improved ability to deliver GM crops to smallholder farmers. We find that although PPP research has focused on crops and traits more relevant for smallholder farmers, many of these efforts have been suspended, with only one crop thus far reaching the hands of farmers. PPPs can address some issues related to GM crop development but still appear constrained by other institutional challenges, which may limit their development, reach, and the achievement of targeted benefits for smallholder farmers.